2003
DOI: 10.1034/j.1600-0404.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recently diagnosed multiple sclerosis on quality of life, anxiety, depression and distress of patients and partners

Abstract: Both patients and their partners demonstrated high levels of anxiety and distress in the early period after the diagnosis. These findings indicate careful attention by health care professionals to identify those who may benefit from further psychological support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
195
6
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 32 publications
22
195
6
9
Order By: Relevance
“…The first four domains are associated with physical health, and the last four, with mental health. The total score ranges from zero (worst) to 100 (best) 11,12 . Kappa statistic was utilized to verify the level of concordance among the instruments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first four domains are associated with physical health, and the last four, with mental health. The total score ranges from zero (worst) to 100 (best) 11,12 . Kappa statistic was utilized to verify the level of concordance among the instruments.…”
Section: Methodsmentioning
confidence: 99%
“…The Osame's motor disability score (OMDS) grades the motor dysfunction in relation to the gait disturbance 10 . The medical outcomes study short form-36 health survey (SF-36) is the instrument used to assess quality of life 11,12 . This study identifies the functional status of HAM/ TSP patients through the comparison of functional assessment tools.…”
mentioning
confidence: 99%
“…In our study, females with MS reported slightly more symptoms of anxiety than did males (22 There are few robust epidemiological studies addressing anxiety in MS using standardized and validated outcome measures. In addition to their own results, Nicholl et al reviewed past research on emotional problems in people who have MS.…”
Section: Discussionmentioning
confidence: 65%
“…Eight months after diagnosis of MS, 34% of the patients reported that they experienced high levels of anxiety. In a follow-up study two years later, 69% of persons with MS with high anxiety scores at baseline still had high scores [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Causes of depression and anxiety in this patient population include MS-related processes, genetic and environment-related predisposition, normal grieving and adjustment to loss [10,11]. Although depression and anxiety tend to worsen as physical disability increases [12], psychiatric comorbidities such as depression and anxiety are frequently present at the time of MS diagnosis [2,3,8,13].…”
Section: Introductionmentioning
confidence: 99%